2021
DOI: 10.1177/00048674211025703
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors of Internet gaming disorder among Chinese people: A meta-analysis

Abstract: Objectives: Effective prevention and intervention of Internet gaming disorder require the identification of risk and protective factors. This study aims to exhaustively review the risk and protective factors of Internet gaming disorder among Chinese people. Method: We searched for articles published from database inception to February 2020 in MEDLINE, PsycINFO, Embase, PubMed, Web of Science and two Chinese databases, CNKI and Wanfang Data. Studies were included in the meta-analysis if they addressed Internet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 87 publications
(103 reference statements)
11
20
0
Order By: Relevance
“…In addition to replicating the positive relationship between DER and SMAs ( Ji et al, 2021 , Marchica et al, 2020 ), the present study further identified neural activations during loss anticipation as an underlying neural mechanism that accounted for the association between DER and SMAs. Specifically, activations in the AI and DLPFC during loss anticipation served as linking mechanisms in the associations between DER and SMAs.…”
Section: Discussionsupporting
confidence: 77%
“…In addition to replicating the positive relationship between DER and SMAs ( Ji et al, 2021 , Marchica et al, 2020 ), the present study further identified neural activations during loss anticipation as an underlying neural mechanism that accounted for the association between DER and SMAs. Specifically, activations in the AI and DLPFC during loss anticipation served as linking mechanisms in the associations between DER and SMAs.…”
Section: Discussionsupporting
confidence: 77%
“…Ostinelli et al (2021) reported pooled prevalence of 32% for comorbidity of depression and pooled BDI score of 10.31 in individuals with significant IGD symptoms. A recently published meta-analysis by Ji et al (2021) summarized the risk and protective factors of IGD in a Chinese population. They identified maladaptive cognitions, achievement motivation, and rule-breaking behavior as the strongest risk factors, while selfcontrol, school climate, and school engagement seemed to act protectively.…”
Section: Risk and Protective Factors For (Internet) Gaming Disorder: ...mentioning
confidence: 99%
“…A recent meta-analysis on risk and protective factors by Ropovik and colleagues 21 reported pooled associations of the seven motives to IGD between 0.08 and 0.42 (escape r = 0.42, fantasy r = 0.32, coping r = 0.30, competition r = 0.24, skill development r = 0.21, social r = 0.19, recreation r = 0.08). A second meta-analysis replicated the strongest association of IGD with the escapism motivation 55 , whereas a third found the escapist association to be slightly surpassed by achievement motivation in the Chinese population 36 .…”
Section: Introductionmentioning
confidence: 85%
“…Since mere time spent on gaming was found to be a poor predictor of negative health outcomes of players and IGD 30 34 , research has explored associated risk and protective factors. IGD appeared associated with younger age 10 , 35 37 and male sex 11 , 13 , 16 , 19 , 21 , 36 , 38 .…”
Section: Introductionmentioning
confidence: 95%